Adaptações cardiovasculares e autonômicas em pessoas pós-AVC submetidos a exercício aeróbico: uma revisão sistemática com meta-análise - Feltrin, Marluci (2024)
Stroke has been considered the third leading cause of death and disability. Following a stroke, due to the brain-heart interaction, numerous changes in the morphology and physiology of the heart and blood vessels may occur. Aerobic Exercise (AE) has been recommended as a key component in the treatment for the physical conditioning of individuals who have had a stroke and also as a means to increase physical activity levels in this population. Objective: Characterize through systematic review the adaptations of cardiac and autonomic function in post-stroke individuals undergoing aerobic exercise. Methodology: This is a systematic literature review and meta-analysis. The risk of bias in the studies was assessed using the Cochrane Collaboration tool. Randomized clinical trials with post-stroke patients undergoing aerobic exercise with heart rate monitoring were included in the eligibility criteria. The review protocol was registered with PROSPERO (CRD42023460570). Results: A total of 10,747 studies were initially identified, 8,068 were excluded after title and abstract reading, 67 were read in full, and 7 studies were included for analysis. A total of 301 volunteers were randomized to aerobic exercise training or control group, with 168 volunteers having ischemic stroke and 94 having hemorrhagic stroke. The exercises performed included treadmill, ground/pool walking, and cycle ergometer, with intensity control ranging from moderate to high (above 70% of heart rate reserve). The intensity of interventions in the control group was considered light (<40% of heart rate reserve). All seven studies were classified as low risk of bias. A total of 4 studies were included in the meta-analysis, and for all investigated variables, a null effect of the intervention was suggested, as all points touched the zero axis. GRADE analysis was not conducted in this study due to the very low number of included studies and the detected null effect. Conclusion: Considering the criteria of this review, aerobic exercise was not able to induce improvement in the cardiovascular system of individuals who had a stroke; however, further studies are needed to investigate cardiovascular adaptations in individuals who have had a stroke.